2018
DOI: 10.1371/journal.pone.0206642
|View full text |Cite|
|
Sign up to set email alerts
|

Axon numbers and landmarks of trigeminal donor nerves for corneal neurotization

Abstract: PurposeCorneal anesthesia leads to chronic corneal injury. This anatomical study characterizes the donor nerve branches of the supratrochlear and supraorbital nerves used for corneal neurotization.MethodsIn 13 non-embalmed cadavers, the supratrochlear and supraorbital nerves were dissected and distances to anatomical landmarks measured. Cross-sections of supratrochlear and supraorbital donor nerves were harvested and histomorphometrically analyzed to assess the number of myelinated axons.ResultsThe donor axon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Through dissection of non-embalmed cadavers, they found that the mean donor axon counts were 3146 ± 1069.9 for the supratrochlear nerve and 1882 ± 903 for the supraorbital nerve. Consequently, the supratrochlear and supraorbital nerves, both sensory nerves, can be considered potent donor nerves for ocular neuropathologies [54].…”
Section: Discussionmentioning
confidence: 99%
“…Through dissection of non-embalmed cadavers, they found that the mean donor axon counts were 3146 ± 1069.9 for the supratrochlear nerve and 1882 ± 903 for the supraorbital nerve. Consequently, the supratrochlear and supraorbital nerves, both sensory nerves, can be considered potent donor nerves for ocular neuropathologies [54].…”
Section: Discussionmentioning
confidence: 99%
“…Domoshek et al compared the distal supraorbital to the supratrochlear nerve, indicating that the former contains approximately 1000 more axons than the latter (3146 ± 1069 versus 1882 ± 903), which is an important consideration in direct reinnervation techniques [ 76 ]. If the supraorbital nerve is approached very proximally, just above the orbital rim, it contains yet more axons, suggesting that connecting the nerve (or coaptation) to a nerve graft should be done as proximal as possible to maximize the axonal load [ 77 ]. The same study by Domoshek et al reported that the sural nerve, harvested as a conduit graft, contained 3176 ± 1524.5 myelinated nerve fibres.…”
Section: Cadaveric Studies Underlying Corneal Neurotizationmentioning
confidence: 99%